Sonar measurements in ship wakes simultaneous with TerraSAR-X overpasses - Soloviev, Alexander; Gilman, Mikhail; Young, Kathryn; Brusch, Stephan; Lehner, Susanne (IEEE Transactions on Geoscience and Remote Sensing, 2010)
A pilot experiment was conducted in the period from April to June 2008 in the Straits of Florida near Port Everglades, Florida, in order to study the dynamics of far wakes of ships. In this experiment, a small boat with downward-looking sonar made snakelike sections through wakes of ships of opportunity during the TerraSAR-X overpasses. The ship and its parameters (length, speed, course, etc.) were identified utilizing an automated identification system. The sonar responded to the clouds of microbubbles generated in the ship wake by the propulsion system and ship-hull turbulence. The ship wakes were traced in the sonar signal typically from 10 to 30 min after the ship's passage. A preliminary analysis of the measurements suggests that the visibility of the centerline ship wake in synthetic aperture radar (SAR) images is correlated with the presence of microbubbles in the wake. This supports the hypothesis that natural surfactants scavenged and brought to the surface by rising bubbles play an important role in the wake visibility in SAR. The influence of the wind-wave field on the ship wake, as well as the effect of screening of the wind-wave field by the ship's hull, adds another level of complexity to wake patterns observed in SAR images. © 2009 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Geophysical measurements; Remote sensing; Sonar imaging; Synthetic aperture radar (SAR)